Supramolecular Approach to Tuning the Photophysical Properties of Quadrupolar Squaraines - Kaczmarek-Kȩdziera, Anna; Ośmiałowski, Borys; Żuchowski , Piotr S.; Kȩdziera, Dariusz (Frontiers in Chemistry, 2022)
In the present study, the influence of the hydrogen bonding for the one- and two-photon absorption of the prototypical squaraine dye is investigated with quantum chemistry tools. The central squaraine unit is bound by the strong hydrogen bonds with the 4-substituted N,N'-diphenylurea and, alternatively, N,N'-phenylthiourea molecules what affects to the high extend the properties of the squaraine electron accepting moiety thus shifting its maximum absorption wavelength and enhancing the TPA cross section. The replacement of oxygen by sulfur atoms in the squaraine central ring, known to affect its photophysical behavior, is considered here as the way of modifying the strength and nature of the intermolecular contacts. Additionally, the influence of the oxygen-by-sulfur replacement is considered also in the N,N'-diphenylurea moiety, as the factor affecting the acidity of the N-H protons. The introduction of the sequence of the substituents of varying electron-donating or electron-withdrawing character in the position 4 of N,N'-diphenyl(thio)urea subsystems allows to finely tune the hydrogen-bonding with the central squaraine unit by further modification of the N-H bond characteristics. All of these structural modifications lead to the controlled adjustment of the electron density distribution and thus the properties affected such as transition moments and absorption intensity. Ab initio calculations provide the strong support for this way of tailoring of one- or two-photon absorption due to the obtained strong hypsochromic shift of the maximum one-photon absorption wavelength observed particularly for the thiosquaraine complexes and an increase of the TPA wavelength together with the rise of the TPA cross-section. Moreover, the source of the strong modification of the thiosquaraine OPA in contrast to the pristine oxosquaraine upon N,N'-diphenyl(thio)urea substitution is determined. Furthermore, for the first time the linear dependence of the non-additivity in the interaction energy on the Hammett substituent constant is reported. The stronger the electron-donating character of the substituent, the larger the three-body non-additive components and the larger their percentage to the total interaction energy.